Development of pH indicator film containing butterfly pea flower (Clitoria ternatea L.) extract for monitoring sardines and catfish freshness during chilled storage - Mohammad Saiful Anwar Mohd Yunus,; Nur Nabilah Hasanah,; Ezzat Mohamad Azman,; Sumarto, Sumarto; Jamilah Bakar,; Mohammad Rashedi Ismail-Fitry, (Penerbit Universiti Kebangsaan Malaysia, 2025)
An application of pH indicator film has been utilised in food packaging to ensure quality and safety, as well as monitor the real-time freshness of perishable products; however, previous works have focused on synthetic dyes. This research aimed to develop and determine the physicochemical characteristics of a pH indicator film from potato starch incorporated with butterfly pea anthocyanin extracts (PS-BPE) at different concentrations of BPE (4%, 8% & 12%), and evaluate its potential for monitoring the freshness of sardines and catfish. The films were characterised by microstructure, thickness, moisture content (MC), water vapour permeability (WVP), and colour responses at different pH values (2 - 12). Then, the PS-BPE films were applied to fish to monitor the freshness at 4°C for 6 days of storage. The colour changes, pH, texture profile analysis (TPA), and Quality Index Method (QIM) were analysed every two days of storage. The increase in BPE concentration in the film results in an increased thickness and a decreased MC, with no significant difference in WVP of the film. The colour of PS-BPE films also became significantly darker and bolder with an increase in concentration, and colour changes from purple to blue-green were observed during storage. TPA show no difference between the two fish samples. However, both fish increased in pH and QI scores over time, indicating a decline in the quality and freshness of the fish as the storage period extended. These results suggest that PS BPE films have the potential to serve as a freshness indicator for fish samples.